Pemahaman dan Kepedulian dalam Implementasi Green Accounting oleh UMKM Pencucian Mobil - Saskia Heni Juita; Carolyn Lukita; Lilis Lasmini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research explores the understanding and implementation of green accounting in SMEs in the car wash sector. This study uses in-depth survey methods and interviews with car wash MSME owners in various locations,focusing on environmental impacts and sustainable practices. SMEs in this sector have significant potential to reduce negative environmental impacts through the adoption of green accounting, which involves measuring and reporting the environmental impacts of business activities. A good understanding of green accounting is necessary to integrate sustainable practices such as environmentally-friendly water and chemical management. Despite ample research supporting the benefits of green accounting, its implementation in SMEs remains limited and faces challenges such as knowledge constraints and institutional support. Environmental awareness and compliance with environmental regulations are also crucial for creating environmentally sustainable businesses. By understanding and addressing these barriers, SMEs in the car wash sector can actively contribute to balancing economic, social, and environmental concerns. Adequate education and guidance are needed to support SME owners in effectively adopting green accounting. This research aims to provide insights for policymakers and SME owners on the importance of green accounting in achieving sustainable business practices.